Structural elements of online service product quality. (1st September 2004) - Cook, David P.; Dave, Dinesh S.
The Internet is at the centre of a whirlwind of economic hype and activity with more and more adults going online both at home and work. An increasing proportion of retail sales is being conducted online, and is expected to continue to increase for the foreseeable future. The combination of the proliferation of online retail sales and the recent shakeout of internet firms, is a clear indicator that significant opportunities exist online; but not without lurking dangers. What differentiates the successful internet player from the also ran? This article posits that one differentiating factor is the ability to successfully deliver high quality service products. A service quality stack is developed that demonstrates the interplay between the service product delivery system, service quality judgment criteria, and an underlying infrastructure based on the following empirically identified elements: methods standardisation, customer contact, and customer involvement.